MANAGING THE PROCESS OF DEVELOPING THE PROFESSIONAL COMPETENCE AND CREATIVITY OF EDUCATORS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
As the modern education and upbringing system develops, the role of the educator and his professional competence, as well as his creativity in creating and introducing innovations, are becoming increasingly important. The educator not only directly affects the spiritual and intellectual development of the child's personality, but is also one of the main figures in creating a favorable environment for their comprehensive development. One of the main factors determining the effectiveness of the educator's activities is his professional competence and creative abilities. These two concepts are of fundamental importance in increasing the efficiency of the process of working with children, developing their independent thinking and preparing them for life.